The Small Fire Detection Using Rgb Method Of Himawari-9 And Firms Satellite Imagery (Fire Information Resource Management System) Using Viirs And Modis Satellite Imagery In Medan Marelan (Case Study: 16 November 2023) - Giananti, Attiya Shakila; Haryanto, Yosafat Donni; Sopacua, Jerremy Mezac (Universitas Negeri Semarang, 2025)
Medan City is a city with a dense population. This causes residential areas in Medan Marelan tend to be densely packed. The negative impact is that are prone to fire disasters. To prevent the impact of these fires, monitoring is needed. Way of monitoring that can be done is using remote sensing. This research carried out remote-sensing by using the Himawari-9, MODIS, and VIIRS satellites. The method used are the Red Green Blue (RGB) method for the Himawari-9 satellite and the Fire Information Resource Management System (FIRMS) method for the MODIS and VIIRS satellites. Based on this research, the MODIS and VIIRS satellites are superior in monitoring small fires that occurred in Medan Marelan compared to the Himawari-9 satellite. The Himawari-9 satellite is more likely to detect clouds over fire locations than the fire itself. This was proven by radiosonde data which stated that atmospheric conditions at that time were moderately unstable. With additional information via rainfall data on November 16 2023 with a range of 20-50 mm.